Life Experiences of Spouses of Persons Living with Schizophrenia. - Fathima P.S. (Journal of Social Work Education and Practice, 2023)
Schizophrenia is a brain disorder, which affects the way a person acts, thinks, and sees the world. Understanding the life experiences of spouses of persons living with schizophrenia will help the professionals understand the challenges they face while taking care their loved ones. It will be useful in developing special programmes in order to enable them to provide better care to their loved one and also face the challenges that they may come across. This study is in focus of this aim and for a better understanding, researcher adopted qualitative approach to conduct the study.